Sociology for the 21st century - Curry, Timothy J. (Timothy Jon), 1943-; Jiobu, Robert; Schwirian, Kent. (Upper Saddle River, NJ : Prentice Hall, 1999)
Perspective and method. Social inequality. Social institutions. Working for change.
Keywords: Sociology; Sociology; Social change; Sociology -- United States; Social change -- United States; United States -- Social conditions